Pharmacognostical standardization and quantitative estimation of amino acid in Alternanthera Sessilis - SWARNAKUMARI.S; MOHAN. S (International Journal of Pharma and Bio Sciences, 2019)
The present study was aimed to scientifically develop a standard monograph for leaves of Alternanthera sessilis on the grounds of pharmacognostical and phytochemical aspects. Pharmacognostically, the leaf evaluation was done by employing standard parameters and also amino acid quantification was accomplished. Macro- microscopical characters, fluorescence analysis, extractive value, ash values and preliminary phytochemical tests divulged the characteristic features of the drugs. The solvent extracts were subjected to a preliminary phytochemical screening for detection of chemical principles present in leaves and revealed the presence of carbohydrates, glycosides, alkaloids, proteins and amino acids, flavonoids, terpenoids, tannins and phytosterols. Amino acids present in the fresh leaves of Alternanthera sessilis were isolated and the percentage yield of aspartic acid (0.014 % w/w), cysteine (0.042 % w/w), glycine (0.021 % w/w) and proline (0.048 % w/w) were quantified by using ninhydrin method. The diagnostic characters obtained from the leaves of Alternanthera sessilis will provide beneficial information in identification of the plant and depart it from other closely related Alternanthera species.